Function and Regulation of Agrobacterium tumefaciens Cell Surface Structures That Promote Attachment - Thompson, Melene A. (Curr Top Microbiol Immunol, 2018)
Agrobacterium tumefaciens attaches stably to plant host tissues and abiotic surfaces. During pathogenesis, physical attachment to the site of infection is a prerequisite to infection and horizontal gene transfer to the plant. Virulent and avirulent strains may also attach to plant tissue in more benign plant associations, and as with other soil microbes, to soil surfaces in the terrestrial environment. Although most A. tumefaciens virulence functions are encoded on the tumor-inducing plasmid, genes that direct general surface attachment are chromosomally encoded, and thus this process is not obligatorily tied to virulence, but is a more fundamental capacity. Several different cellular structures are known or suspected to contribute to the attachment process. The flagella influence surface attachment primarily via their propulsive activity, but control of their rotation during the transition to the attached state may be quite complex. A. tumefaciens produces several pili, including the Tad-type Ctp pili, and several plasmid-borne conjugal pili encoded by the Ti and At plasmids, as well as the so-called T-pilus, involved in interkingdom horizontal gene transfer. The Ctp pili promote reversible interactions with surfaces, whereas the conjugal and T-pili drive horizontal gene transfer (HGT) interactions with other cells and tissues. The T-pilus is likely to contribute to physical association with plant tissues during DNA transfer to plants. A. tumefaciens can synthesize a variety of polysaccharides including cellulose, curdlan (β−1,3 glucan), β−1,2 glucan (cyclic and linear), succinoglycan, and a localized polysaccharide(s) that is confined to a single cellular pole and is called the unipolar polysaccharide (UPP). Lipopolysaccharides are also in the outer leaflet of the outer membrane. Cellulose and curdlan production can influence attachment under certain conditions. The UPP is required for stable attachment under a range of conditions and on abiotic and biotic surfaces. Other factors that have been reported to play a role in attachment include the elusive protein called rhicadhesin. The process of surface attachment is under extensive regulatory control, and can be modulated by environmental conditions, as well as by direct responses to surface contact. Complex transcriptional and post-transcriptional control circuitry underlies much of the production and deployment of these attachment functions.